Comparison of two rapid microscopic methods and culture for detection of Chlamydia trachomatis in ocular and nasopharyngeal specimens from infants. - Roblin, P M (1989)
The data available for the diagnosis of chlamydial infections in infants which compare direct fluorescent-monoclonal-antibody stains (DFAs) with culture are limited to one reagent, MicroTrak (Syva Inc., Palo Alto, Calif.). We therefore performed a comparison of Pathfinder (Kallestad Diagnostics, Chaska, Minn.) and MicroTrak with chlamydia culture. Paired conjunctival and nasopharyngeal specimens for DFAs and cultures were obtained from 56 infants less than 1 month of age with conjunctivitis. The sensitivities for detecting C. trachomatis in conjunctival specimens with MicroTrak and Pathfinder were 93.8 and 88.2%, respectively, and the specificities were 87.5 and 94.9%, respectively. The DFA tests on nasopharyngeal specimens from infants with conjunctivitis did not perform as well. The sensitivities for Pathfinder and MicroTrak were 33 and 50%, respectively. There were a total of six patients with culture-positive chlamydial conjunctivitis whose nasopharyngeal specimens were DFA positive and culture negative; four of the specimens were positive by both DFAs. These six discordant specimens were further evaluated by preparing pellets and smears of the original culture specimens. All six contained typical fluorescing elementary bodies when stained with the Syva DFA reagent.